1975
DOI: 10.2136/sssaj1975.03615995003900050025x
|View full text |Cite
|
Sign up to set email alerts
|

Redox Potential in Irrigated Desert Soils as an Indicator of Aeration Status

Abstract: The redox potential (Eh) of irrigated desert soils was evaluated under a wide range of conditions. Factors important in controlling Eh were temperature, flooding time, soil water content, and energy source. Field heterogeneity necessitated using 10 to 20 electrodes (placed in a 30‐cm square) to characterize a treatment. The Eh varied over a short distance with variations not due to poisoning or erratic electrode readings.A 5C increase in temperature at the 15‐cm depth resulted in a 50‐mV decrease in redox pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Nesse sentido, Meek & Grass (1975) A concentração de N foi significativamente menor no período de maior inundação (fevereiro), em todas as profundidades de amostragens e nas duas áreas estudadas (Quadro 2). Em solos ácidos e anaeróbios com pH menor que 5,5, a taxa de nitrificação é muito baixa, o que resulta em acumulação de amônia (NH 3 ), que pode ser perdida por volatilização, ou amônio (NH 4 + ), devido à pequena disponibilidade de O 2 necessário à conversão microbiana da amônia em nitrato .…”
Section: Atributos Químicos Do Solo Considerando a Variação Temporal unclassified
“…Nesse sentido, Meek & Grass (1975) A concentração de N foi significativamente menor no período de maior inundação (fevereiro), em todas as profundidades de amostragens e nas duas áreas estudadas (Quadro 2). Em solos ácidos e anaeróbios com pH menor que 5,5, a taxa de nitrificação é muito baixa, o que resulta em acumulação de amônia (NH 3 ), que pode ser perdida por volatilização, ou amônio (NH 4 + ), devido à pequena disponibilidade de O 2 necessário à conversão microbiana da amônia em nitrato .…”
Section: Atributos Químicos Do Solo Considerando a Variação Temporal unclassified
“…The O 2 consumption rates are a function of both the quantity and quality of OC (Yiqi and Zhou, 2010). Incorporation of organic material can substantially increase soil respiration and O 2 demand (Meek and Grass, 1975; Flessa and Beese, 1995). In batch microcosms using grenade range soil from Fort Bragg, NC, TNT was rapidly biodegraded under both aerobic and anaerobic conditions (Won and Borden, 2016).…”
mentioning
confidence: 99%
“…The level of the redox potential depends on several factors in the soil. Meek and Grass (1975) investigated the effect of different factors on the redox potential in irrigated desert soils and found that a decrease in redox potential occurred as a result of (1) an increase in temperature (in the range 0-20 °C), (2) prolongation of the soil saturation time, and (3) higher amounts of substrate added to the soil. These findings all indicate that the changes in redox potential are due to microbial activity.…”
Section: Redox Potential In Soil Sciencementioning
confidence: 99%